2010
DOI: 10.1007/s00246-010-9868-5
|View full text |Cite
|
Sign up to set email alerts
|

Left-Ventricular Noncompaction in a Pediatric Population: Predictors of Survival

Abstract: Left-ventricular noncompaction (LVNC) is an echocardiographic finding of increasing frequency in pediatrics; however, predictors of outcomes have been difficult to identify. We conducted a retrospective review of pediatric patients at the Morgan Stanley Children's Hospital of New York from January of 1993 to September of 2009 to identify predictors of the primary outcome of death or heart transplantation. LVNC was identified in 50 patients, 34 of them < 1 year of age. Death or transplantation occurred in 26 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 13 publications
2
23
0
1
Order By: Relevance
“…Previous studies have shown that LVNC appears to be more commonly associated with right-sided disorders including Ebstein's anomaly and tricuspid atresia. Less frequently it has been reported among patients with aortic coarctation, tetralogy of Fallot, and bicuspid aortic valves, as well as septal defects [7,9,11,12]. The present study expands upon these previous findings by noting that the distribution of CHD lesions was diverse and included many congenital heart defects that have not been routinely associated with LVNC, such as coarctation of the aorta, double inlet left ventricle, and ventricular septal defects.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Previous studies have shown that LVNC appears to be more commonly associated with right-sided disorders including Ebstein's anomaly and tricuspid atresia. Less frequently it has been reported among patients with aortic coarctation, tetralogy of Fallot, and bicuspid aortic valves, as well as septal defects [7,9,11,12]. The present study expands upon these previous findings by noting that the distribution of CHD lesions was diverse and included many congenital heart defects that have not been routinely associated with LVNC, such as coarctation of the aorta, double inlet left ventricle, and ventricular septal defects.…”
Section: Discussionsupporting
confidence: 57%
“…Criteria for diagnosis varies in the literature, but most agree, to make the diagnosis, there must be prominent trabeculations and inter-trabecular recesses that communicate with the left ventricular cavity [2,8]. Myocardial abnormalities consistent with LVNC cardiomyopathy have been reported in association with some forms of structural CHD [7,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent retrospective review of 50 children with LVNC found 23 (46%) also had DCM. 28 Death or transplant occurred in 16 (59%) of the children with LVNC and DCM; half of the entire group of 50 children died within 1.2 years of presentation. Time to death or transplant was not reported for the LVNC with DCM subgroup.…”
Section: Discussionmentioning
confidence: 98%
“…Although the cause of this arrest is unknown, LV noncompaction has been associated with other congenital heart defects. Zuckerman et al found 13 out of 58 (22%) patients with LV noncompaction had another form of congenital heart defect, most commonly ventricular septal defects (seven out of 13), followed by secundum atrial septal defects (three out of 13) [94]. Other abnormalities associated with LV noncompaction include Ebstein’s anomaly, hypoplastic right ventricle and hypoplastic left heart syndrome [81].…”
Section: Noncompaction In Childhoodmentioning
confidence: 99%